A design of fuel control unit for eco vehicle engines - Nguyen , Trong Thuc (Journal of Technical Education Science, 2021)
Nowadays, solution of fuel injection is the best way for design of fuel economy vehicle while mechanical improvement has almost reached its limit. This article shows result of the research and making the fuel injection electronic control unit (ECU) used for two annually contests named Honda EMC and Shell ECO-marathon. The control circuit is designed and coded with Arduino Mega, sensors and actuators equipped in popular cars. The circuit also allows users to change the fuel injection map and the ignition timing map to suit ECO vehicle, its necessary data help driver to have better seeing and adjusting during contest time. This permit contestant teams to modify base on their design and showed data can help contest process become more optimized and simply.